Proximate composition, phytochemical screening and anti-hyperglycemic effect of elephant foot yam (Amorphophallus paeoniifolius) tuber on alloxan induced diabetic rats - Rahman, Shaikh Shahinur; Muhsin, Mir Mohammad; Karim, Md. Rezaul; Zubaer, Md.; Rahman, Md. Hafizur; MA. Rouf, Shakh (Progress in Nutrition, 2021)
Summary. Purpose: The objectives of this study were to explore the nutrient analysis of elephant foot yam tuber and also observe the anti-hyperglycemic effect on both diabetic and non-diabetic rats. Methods: Healthy adult Long Evans rats were grouped into four, and each group had six rats. Diabetes was induced intraperitoneally by injecting 140 mg/kg body weight of alloxan dose, and 500 mg/kg bd.wt of Amorphophallus paeoniifolius powder was administered orally for six weeks of both diabetic and non-diabetic experimental rats, and next three weeks supplementary feeding were pulled out. Results: The proximate nutritional composition showed that elephant foot yam is a good source of dietary complex carbohydrate, fiber, minerals such as- calcium, phosphorous, potassium and zinc as well as phytochemicals. This tuber was investigated for the presence of 25 anti-diabetogenic phytochemicals. Among them, 17 phytochemicals were detected in elephant foot yam but eight phytochemicals viz- anthraquinone, carotenoid, cardiac glycoside, glycoside, phlobotanin, phenol, saponin and tannin were not found. Fasting blood glucose (FBG) level was reduced remarkably (p